Pendeteksi Persentase Kadar Alkohol Dengan Kontrol PID Berbasis IOT - Ayu Handira, Putri; Azis Pangestu, M; Sulistyo, Eko; Silalahi, Parulian (Jurnal Inovasi Teknologi Terapan, 2023)
In order to find out the alcohol content in drinks circulating in the community, measurements and tests are usually carried out in the laboratory. This takes quite a long time. To solve this problem, we need a tool that can measure alcohol quickly and accurately. This research aims to design and manufacture a detector for the percentage of alcohol content, especially in drinks, using an IoT (Internet of Thing)-based MQ3 sensor as a monitoring system that is connected directly to a smartphone. The method used in this research is PID (Proportional Integral Derivative). By setting the PID tuning with a value of kp=4, ki=3, kd=0.0001 and a setpoint of 210 is used to produce an optimal reading of the alcohol content in the drink. Readings using PID control have an average error value of 1.26%, otherwise without using PID control, the average error value is 8.12%. In order to see the alcohol content of the experimental results of the type of drink detected, it will be displayed on the blynk application on the smartphone.